Relevansi Nilai Informasi Akuntansi Di Indonesia Berdasar Simple Accounting-Based Fundamental Analysis - Nugroho Wisnu Murti; Indriyana Widyastuti (Jurnal Akademi Akuntansi, 2023)
Decreasing the value relevance of accounting information issues cannot be separated from complexity of accounting standards and their implementation. This phenomenon is our motivation to examine whether the valuation model on the prospects of companies that prioritize the parsimony principle by using accounting information also indicates a decrease in the relevance of accounting information in Indonesia. We examined the f-score indicator which is referred to as a simple accounting-based fundamental analysis. This study observed all financial statements of issuers in Indonesia from 2006 to 2019 and their share prices in the secondary market during year t+1.We used multiple regression to estimate the value of r-square in each year of observation. This study could not find any indication of a decrease in the value relevance of accounting information during the observation period based on the r-square which is estimated by the f-score indicator. This finding can be a part of an empirical study that is not only related to value relevance, but also to the topic of accounting information readability.